Evaluation of Chitosan Gel on Burn Wound Healing and Keratinocytes Function: Effect of Chitosan Gel on Burn Wound Healing - Ansari, Mojtaba (Iranian Journal of Pharmaceutical Sciences, 2020)
Skin burns are common skin injuries that can result from exposure to various sources of heat by which, depending on the cause, different degrees of burns are generated. In restoration of superficial burns by reepithelialization, the skin is rebuilt, but the skin color is different than the healthy tissue. Keratinocytes represent the major cells of the epidermis. These cells are sourced from ectoderm and are continuously being formed from the basal level. The main task of these cells is to make the protein keratin. During differentiation, keratinocytes move toward the superficial layers of the epidermis and generate more keratin. These cells are colorless, but by manipulating melanocytes (the melanocyte cells produce pigment in the skin), one can control the darkness degree of the skin. Keratinocytes, in particular, produce chemical signals which, in turn, are responsible for regulating the distribution and amount of melanin pigment in melanocytes. In this study, using an aluminum stamp weighing 85 grams, at a temperature of 80 ◦C, superficial burns, of 2nd degree, were generated on six rabbits. The rabbits were divided into two groups; a control group and the second one in which a chitosan (CHI) gel was used as a dressing. After treatment, histopathology tests and the TEM results confirmed that, in the CHI treatment group, the restoration led to acceptable results. It was shown that if the repair was performed with a CHI based gel, the keratinocyte appeared with their original structure after restoration, but if the treatment was done without the CHI dressing, the number of these cells increased, more stimulation of melanocytes occurred and, ultimately, it led to an unwanted color change of the burnt area.